2017
DOI: 10.1021/acs.jafc.6b05651
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Cryoprotective Roles of Carrageenan Oligosaccharides in Peeled Whiteleg Shrimp (Litopenaeus vannamei) during Frozen Storage

Abstract: The cryoprotective effects of carrageenan oligosaccharides on peeled whiteleg shrimp were investigated and compared with sodium pyrophosphate treatment during frozen storage, primarily the interaction mechanisms between oligosaccharides and shrimp myosin. Data revealed significant profitable effects on water-holding capacity and textural variables in oligosaccharide-treated shrimp compared to the control. Chemical analyses showed that these saccharides maintained a higher myofibrillar protein content and Ca-AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…They reported that the saccharides substituted the water molecules around the shrimp myosin surface by forming hydrogen bonds with polar residues of amino acids and stabilized the protein during frozen storage. A similar phenomenon was observed for the interaction of TRH and alginate with shrimp myosin through MD simulation (Zhang, Yang et al., ). This mechanism can also describe the protection of xylooligosaccharides on peeled shrimps (Zhang, Hao et al., ).…”
Section: Simulations To Evaluate the Dynamic Behaviors Of Componensupporting
confidence: 77%
“…They reported that the saccharides substituted the water molecules around the shrimp myosin surface by forming hydrogen bonds with polar residues of amino acids and stabilized the protein during frozen storage. A similar phenomenon was observed for the interaction of TRH and alginate with shrimp myosin through MD simulation (Zhang, Yang et al., ). This mechanism can also describe the protection of xylooligosaccharides on peeled shrimps (Zhang, Hao et al., ).…”
Section: Simulations To Evaluate the Dynamic Behaviors Of Componensupporting
confidence: 77%
“…Myofibrillar Ca 2+ ‐ATPase activity was analyzed according to the procedure published by Zhang, Yang, et al (). MPs were incubated at 30°C for 5 min in pH 7.0 Tris‐maleate buffer in the presence of 20 mmol/L adenosine 5â€Č‐triphosphate and 0.10 mol/L CaCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the increase in Ca 2+ ‐ATPase activity of carrageenan and its oligosaccharide treatments might be related to the hydrophilic hydroxyl group located on the saccharide chains. Noncovalent forces combine hydroxyls with water molecules, which downregulate ice crystal formation and development in the mud mixture and avoid the conformational structure disruption and MP interactions (Zhang et al., 2017). Other studies have suggested that saccharides, such as konjac glucomannan, alginate oligosaccharides, trehalose, and sodium lactate, could effectively alleviate the reduction of myofibrillar Ca 2+ ‐ATPase activity (Gao et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, saccharides can also interact with other proteins, such as porcine myosin protein (Teng, Guo, Yuan, Song, & Ren, 2017) and ÎČ‐lacto‐toglobulin (Baussay et al., 2007). We previously evaluated the antioxidant activities and cryoprotective actions of carrageenan oligosaccharides in shrimp muscle tissues and found that carrageenan oligosaccharides reduced drip loss, maintained muscle texture and color, and prevented physical damage of shrimp (Zhang et al., 2017; Zhang et al., 2018). However, little information is available on the effects of carrageenan and its derivatives on the functional and physicochemical characteristics of MPs in mashed muscle systems (mashed shrimp, Xia‐Hua) during frozen storage.…”
Section: Introductionmentioning
confidence: 99%